Health systems in high-performance sport: key functions to protect health and optimize performance in elite athletes - Drew, M. K.; Toohey, L. A.; Smith, M.; Baugh, C. M.; Carter, H.; McPhail, S. M.; Jacobsson, J.; Timpka, T.; Appaneal, R. (Sports Medicine, 2023)
Enabling athletes to achieve peak performances while also maintaining high levels of health is contextually complex. We aim to describe what a `health system` is and apply the essential functions of stewardship, financing, provision of services and resource generation to an Australian high-performance sport context. We introduce a fifth function that health systems should not detract from athletes` ability to achieve their sports goals. We describe how these functions aim to achieve four overall outcomes of safeguarding the health of the athletes, responding to expectations, providing financial and social protection against the costs of ill health, and efficient use of resources. Lastly, we conclude with key challenges and potential solutions for developing an integrated health system within the overall performance system in high-performance sport.